Different surface treatment protocols of a Y-TZP ceramic with a superficial glaze layer - Miranda, Jean Soares [UNESP]; de Carvalho, Ronaldo Luís Almeida [UNESP]; Barcellos, Aline Serrado de Pinho [UNESP]; Souza, Rodrigo Othávio Assunção e; Kimpara, Estevão Tomomitsu [UNESP]; Leite, Fabíola Pessôa Pereira (Universidade Estadual de Campinas, 2019)
Aim: evaluate the influence of etching time with hydrofluoric acid on the bond strength of a Yttrium-stabilized polycrystalline tetragonal zirconia (Y-TZP) ceramic with a superficial glaze layer and a resin cement. Methods: Y-TZP blocks were cut to obtain 40 samples. They were distributed into four groups (n = 10): control treated by sandblasting with silica-coated alumina (RS) and three glazed experimental groups with different etching times: GS20s, GS60s and GS100s. Cementation was done with a universal adhesive and a resin cement. Two cement cylinders were made in each block. After thermocycling, the shear bond test was performed. Two extra samples of each group were made to obtain profilometry, scanning electron microscopy, mapping and backscattered electron detector images. Energy dispersive spectrometry and goniometry were also performed. Results: Kruskal-Wallis and Dunn tests demonstrated bond strength differences only between the RS (22.10MPa) and the GS groups (GS20s: 8,10Mpa; GS60s: 10.49MPa; GS100s: 7.53MPa) (p = 0.001), but there was no difference among the experimental groups (p > 0.05). The contact angles were 55.33° (RS); 70.78° (GS100s); 48.20° (GS60s) and 28.73° (GS20s). ANOVA and Tukey test demonstrated similar wettability of RS to GS60s and GS100s (p > 0.05), but all the experimental groups were statistically different between them (p < 0.001). Qualitative image analysis revealed an irregular glaze distribution after etching. The thickness of the remaining glaze layer measured by profilometry was 5±1μm (GS20S), 4±1μm (GS60S) and 3±1μm (GS100s). Conclusion: The etching time of glazed zirconia did not influence the adhesive strength of the ceramic to the resin cement.
Keywords: Dental cements; Glass; Zirconium